TINJAUAN VIKTIMOLOGI TERHADAP TINDAK PIDANAPENIPUAN ARISAN ONLINE - Siti Duwi Lestari; Yusuf Sefudin (Wijayakusuma Law Review, 2023)
Online arisan is a group collection of money using a lottery system that is conducted online or withoutface-to-face contact. This is effective for people who want to join online arisan because it is easy tointeract with online arisan and arouse people's interest in joining online arisan. However, thisconvenience can also have a negative impact, especially regarding the possibility of online arisan.Therefore, the purpose of this paper is to find out how crimes related to victims of online arisan fraud andtheir legal protection efforts in Indonesia. The research method used in this research is NormativeJuridical research. Normative Juridical Research: Normative juridical research uses a statutory approachor secondary material. Article 378 of the Criminal Code regulates this. Although the criminal provisionsregarding fraud are not specifically explained, people who commit online fraud must be held accountablefor their actions by imposing sanctions on the perpetrators